The formation of hidden negative capital in banking: A product mismatch hypothesis - Alexander Kostrov; Mikhail Mamonov (Bank of Finland, Institute for Economies in Transition (BOFIT), 2019)
This paper investigates the phenomenon of hidden negative capital (HNC) associated with bank failures and introduces a product mismatch hypothesis to explain the formation of HNC. Given that troubled banks tend to hide negative capital in financial statements from regulators to keep their licenses, we attempt to capture this gambling behavior by evaluating product mismatches reflecting disproportions between the allocation of bank assets and the sources of funding. We manually collect unique data on HNC and test our hypothesis using U.S. and Russian banking statistics for the 20042017 period (external validity argument). To manage the sample selection concerns, we apply the Heckman selection approach. Our results clearly indicate that product mismatch matters and works similarly in both U.S. and Russian banking systems. Specifically, an increase in mismatch has two e ects: it leads to a higher probability that a bank's capital is negative and raises the conditional size of the bank's HNC. Further, we demonstrate that the mismatch e ect is heterogeneous with respect to bank size being at least partially consistent with the informational asymmetry view. Our results may facilitate improvements in the prudential regulation of banking activities in other countries that share similar features with either the U.S. or Russian banking systems.
URN:NBN:fi:bof-201904041130
Keywords: G21; G33; C34; 330; Bank failure; Hidden negative capital; Product mismatch; Misreporting; Heckman selection model